Squire - Alfageeh, Sara; Shammas, Nadia (Quill Tree Books : HarperAlley, 2022)
As a member of the subjugated Ornu people, Aiza knows the only way she can become a full citizen of the Bayt-Sajji Empire is to become a Knight. When Bayt-Sajji finds itself on the brink of war, Aiza has the opportunity to finally enlist in the competitive Squire training program. She knows she must keep her Ornu background a secret, but when she learns the terrible truth behind the war, she must decide where her loyalties lie: with her people or the Empire.